Lack of association between postactivation potentiation and subsequent jump performance - Pearson, S. J.; Hussain, S. R. (European Journal of Sport Science, 2014)
Postactivation potentiation (PAP) is a strategy that has been used to acutely enhance the performance of explosive activities. Although, isometric maximal voluntary contractions (MVCs) have previously been shown to enhance subsequent explosive performance, no information currently exists regarding (1) the optimal variables (intensity/volume) of a MVC that best elicits a PAP response, and (2) the utilisation of evoked isometric twitch contractions in combination with performance measures to directly ascertain the presence of PAP following a MVC, and its relationship to performance. Thus, the purpose of this study was to (1) investigate the influence of isometric contraction duration on the PAP response, and (2) to determine the relationship between PAP, indicated as potentiation of muscle twitch force and subsequent jump performance following different-duration MVCs. Eight males (age: 21 ± 0.99) were assessed using performance measures [countermovement jumps] and evoked twitch contractions, before and 4 minutes after three different conditioning contractions (CCs), (1) a 3-second MVC (MVC3), (2) a 5-second MVC (MVC5) and (3) a 7-second MVC (MVC7). Following all CCs, peak twitch torque of the knee extensor muscles was found to increase (MVC3, + 3.9%; MVC5, + 9.6%; MVC7, + 5.2%), although not significantly (P > 0.05). No significant increases in jump height, jump power, rate of force development or takeoff velocity were observed following any of the CCs (P > 0.05). There was also a lack of association between the changes in PAP (twitch torque) and jump height following all CCs (MVC3, r = 0.25; MVC5, r = 0.28; MVC7, r = -0.47). These data indicate that PAP as assessed via twitch contractions is not associated with performance measures subsequent to single-set isometric CCs of varying durations.